Knowledge of Road Traffic Accidents among Taxi Drivers in Kathmandu Valley - Thapa, Rashmi; Singh, Matrika; Bartaula, Manita; Sharma, Shakti; Devkota, Nishchal (Journal of Karnali Academy of Health Sciences, 2026)
Background: Kathmandu Valley experiences over 5,500 road traffic accidents annually, causing significant fatalities. Despite taxis being a safer transport option, they are still involved in accidents that is attributed to compromised knowledge related to road traffic accidents (RTAs). This study investigates taxi drivers' knowledge on road traffic accident prevention in Kathmandu Valley.Methods: The study used a cross-sectional design and was conducted across various junctions in Kathmandu Valley during the period of October to December, 2022. A sample of 322 taxi drivers was selected using a purposive method. Data were collected through semi-structured interviews, with pre-testing conducted beforehand. Data were entered into Epi- Data and analyzed using SPSS version 16, with all ethical considerations strictly adhered.Results: The study found that 98% of the drivers were male, with a mean age of 37 years. Most were married, and over half identified as Janajatis. About half had secondary education, and 80% earned less than 50,000 per month. Despite 86% being satisfied with their income, knowledge gaps were evident. On average, 42% had poor knowledge of human-related factors, 62% lacked understanding of vehicular factors, and 20% were incorrect about environmental factors affecting RTAs.Conclusions: The study highlights significant gaps in taxi drivers' knowledge about factors contributing to RTAs. The findings suggest that targeted education programs and stricter regulations could help improve drivers' understanding and potentially reduce RTAs in the future.